Restoration Scotland, 1660-1690 : royalist politics, religion and ideas - Jackson, Clare, 1972- (Studies in early modern cultural, political and social history, 2003)
"In the twilight years of Scottish independence, the Restoration period witnessed both the triumph of Stuart absolutism and the radical Covenanting resistance of the Killing Times' immortalised in presbyterian memory. Restoration Scotland, 1660-1690 presents the first account of this fascinating and dramatic period in Scottish history. It begins with the widespread popular royalism that acclaimed Charles II's return to power in 1660 and concludes by examining the collapse of royal authority that occurred under his brother, James VII & II, and the events of the Williamite Revolution of 1688-1690. In reconstructing the intellectual world of late-seventeenth century Scotland, this book draws on an extensive range of printed and manuscript sources, the majority of which have hitherto often been neglected. Amidst current interest in Scottish political and parliamentary history before 1707, this book emphasises the dynamic and characteristic cosmopolitanism of Restoration intellectual culture as revealed from a range of national, British and Continental perspectives."--Jacket